Vaccination Status and Outcome of Patients at a Dedicated COVID-19 Centre, Delhi, India: A Retrospective Study - Anshuman Srivastava; Abha Sharma; Rajat Jhamb; Subhash Giri; Nikunj Aggarwal (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Coronavirus Disease-2019 (COVID-19) vaccine provides strong protection against transmission, serious illness, hospitalisation, and death. As India carried out robust vaccination drive covering more than two third of its population, the study was aimed to highlight the effects of vaccination status of patient on the outcome of COVID-19 infection. Aim: To describe the relation of vaccination with disease severity and its outcome during the third wave of COVID-19. Materials and Methods: It was a single-centre retrospective, cross-sectional study conducted in a dedicated COVID-19 Hospital (Guru Tegh Bahadur Hospital) in Delhi, India. A total of 257 patients were admitted between 10th January 2022 to 9th February 2022, and 246 were included in the study. For each individual, demographic, and clinical data was collected. Vaccination data was extracted via the CoWin platform which included vaccine type, as well as date of administration. The profile of patients was established based on clinical examination, laboratory data, nursing record and radiological record during the course of hospitalisation. The clinical outcome was described as discharge, length of hospital stays, and in-hospital death in relation to the vaccination status. Statistical analysis was done using Statistical Package for the Social Sciences (SPSS), version 22.0. Results: Total of 246 patients were divided into three groups- 97 were fully vaccinated, 46 were partially vaccinated and 103 were unvaccinated. Both vaccinated and unvaccinated groups had similar percentage of co-morbidities i.e. 61.3% vs 63.5%. Those who were fully vaccinated were more likely to maintain saturation at room air 30.9% vs 26.1% vs 3.9%, had lesser requirements of mechanical ventilation (6.2% vs 15.2% vs 21.4%), shorter duration of hospital stay (4.2 vs 5.3 vs 7.2 days), and lesser mortality (9.3% vs 21.7% vs 33%) as compared to the partially vaccinated and unvaccinated patients respectively. Conclusion: The beneficial effect of the vaccination was observed in severity, mortality, morbidity, and lesser number of hospitalisations. Hence, vaccination coverage was critical in reducing the severity in reducing the and the hospitalisation in third wave of COVID-19.